A multi sensor data fusion approach for creating variable depth tillage zones - Mouazen, Abdul Mounem; Waine, Toby W.; Whattoff, David (Cambridge University Press, 2017)
In this research a multi-sensor and data fusion approach was developed to create variable depth tillage zones. Data collected with an electromagnetic sensor was fused with measurements taken with a hydraulic penetrometer and conventionally acquired soil bulk density (BD) and moisture content (MC) measurements. Packing density values were then calculated for eight soil layers to determine the need to cultivate or not. From the results 62% of the site required the deepest tillage at 38 cm, 16% required tillage at 33 cm and 22% required no tillage at all. The resultant maps of packing density were shown to be a useful approach to map layered soil compaction and guide VDT operations.
Keywords: Variable depth tillage; Data fusion; Bulk density; Packing density